Influencia de los órganos reproductores sobre la fertilidad en vaquillonas mestizas inseminadas en tiempo fijo - Hidalgo Bravo, Gustavo Adolfo (2012)
SUMMARY An experiment was conducted in order to assess body weight and the influences of the different characterizations of heifers reproductive tract and its relation on pregnancy rate in artificial insemination programs at fixed time (IATF). Heifers (n=38) used were crossbreed, body condition at 3-4 (Scale 1 to 5). From 20 to 30 months of age with a body weight of 320 to 400 kilos. On pre sync all heifers were examined by transrectal ultrasound Aquila Vet 7.5 MHZ, which determined the uterine diameter (cm), ovarian area (cm²), ovarian structures area (cm²). Day zero was placed 0.5 mg progesterone intravaginal device, together with an intramuscular injection of 1 mg of Estradiol Benzoate, on day 8 the intravaginal device was removed plus intramuscular administration of 500 mg of D(+) Cloprostenol, on day 9 0.75 mg of benzoate estradiol was applied intramuscular. Inseminating 54-57 hours after the intravaginal device was removed. Pregnancy was diagnosed 60 days after IATF. Data were analyzed using logistic regression, canonical correlation and sensitivity and specificity curves, using the statistical software INFOSTAT, (2008). There were no significant differences (P<0.05) between body weight, uterus, left ovary and ovarian structures, only significant differences in the right ovary. It is concluded that the area of the right ovary positively influences pregnancy rate, as to better forecast threshold to select a crossbreed heifer pregnancy on right ovary function with 4.80 cm² standards, is appropriate.